2013
DOI: 10.1038/ncomms3763
|View full text |Cite
|
Sign up to set email alerts
|

A Ca2+-dependent signalling circuit regulates influenza A virus internalization and infection

Abstract: Various viruses enter host cells via endocytosis, but the molecular mechanisms underlying the specific internalization pathways remain unclear. Here we show that influenza A viruses (IAVs) enter cells via redundant pathways of clathrin-mediated and clathrin-independent endocytosis, with intracellular Ca2+ having a central role in regulation of both pathways by activating a signalling axis comprising RhoA, Rho-kinase, phosphatidylinositol 4-phosphate 5-kinase (PIP5K) and phospholipase C (PLC). IAV infection ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(100 citation statements)
references
References 69 publications
2
97
0
1
Order By: Relevance
“…4B). 10 Furthermore, we also revealed that the virusdependent calcium elevation triggered RhoA activation only at the periphery of the plasma membrane, as visualized by RaichuRhoA (Fig. 5).…”
Section: Visualization Of Small Gtpase Activationmentioning
confidence: 81%
See 3 more Smart Citations
“…4B). 10 Furthermore, we also revealed that the virusdependent calcium elevation triggered RhoA activation only at the periphery of the plasma membrane, as visualized by RaichuRhoA (Fig. 5).…”
Section: Visualization Of Small Gtpase Activationmentioning
confidence: 81%
“…29 The region of RhoA activation was too restricted for the activation to be detected by conventional biochemical methods. 10 Imaging-based techniques might thereby maximize the researchers' ability to visualize such compartmentalized phenomena that have remained undiscovered by conventional approaches.…”
Section: Visualization Of Small Gtpase Activationmentioning
confidence: 99%
See 2 more Smart Citations
“…A signaling pathway involving phosphatidylinositol 3-kinase (PI3K) have been demonstrated to be involved in virus entry by specifically mediating clathrin-independent endocytosis, endosomal maturation, and intracellular transport of viruses [104]. Recently, it has been shown that Ca ?2 plays an indispensable role in IAV internalization by regulating the phosphatidylinositol 5-kinase (PI5K) and phospholipase C (PLC) signaling pathways [105]. These pathways constitute key mechanisms for clathrin-dependent and clathrin-independent endocytosis during virus infection.…”
Section: Endocytosis and Fusionmentioning
confidence: 99%